Handbook of glass in construction - Amstock, Joseph S. (McGraw-Hill, 1997)
Here is the first comprehensive guide to the specification, installation, manufacture, and testing of glass units and windows for construction. Packed with data, descriptions, applications, and illustrations, the book examines all types of glass and insulating glass, including single and dual sealed systems, heat mirror materials, sealant compounds, and swiggle strip and metal edge compounds. You'll also find complete details on safety glass for hurricane-prone regions and for security purposesÑplus a glossary of terms and listings of trade organizations, suppliers, and manufacturers.